ANALISIS TINGKAT KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V DI SDN 4 SUKAMURNI - Khoerun Nisa, Gina; Nuriyanti, Risma; Gunawan, Dani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the level of student learning independence in the subject of social studies of grade V at SDN 4 Sukamurni. The background of this study is based on the finding that there are some students who lack confidence in asking questions and expressing opinions. The research approach used is quantitative with a survey method. The population of this study was all students of SDN 4 Sukamurni using a saturated sampling technique. Data were collected through a Likert scale questionnaire instrument with 15 statement items about student learning independence in the subject of social studies. The research instrument has been tested for validity with a calculated r value of 0.736-0.876 greater than the r table value of 0.433. And has a Cronbach's Alpha value of 0.968 which has high reliability. The results of the study show that the level of student learning independence in the subject of social studies is in the high category with an average percentage of 82.4%. Student learning independence is seen from the ability to learn independently without relying on others, being actively involved in learning, being able to solve problems in learning, and having a strong character of responsibility.